Development and Characterization of Dual Cross-linked Microbeads for Colon Specific Targeting: Release Kinetic Modeling and Gamma Scintigraphy Studies (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The aim of present study is to develop and characterize ionic gelation-based dual Ca2+ and SO42- crosslinkedgel microbeads using blend mixture of biodegradable chitosan and sodium alginate for colon targeting.Methods: Those diclofenac sodium (DS) loaded microbead formulations were prepared by utilizing ionicgelation based polyelectrolyte complexes technique that was effectively dual cross-linked with Ca2+ and SO42- ionscontaining solutions. Results: The result for surface morphology characterization through scanning electronmicroscopy revealed for semispherical and wrinkled shaped rough surfaces of those optimized formulations. Themean particle size of 761.52–895.22 μm, entrapment efficiency 63.45–78.38% of, and percentage yield of 73.28–78.69% are resulted, respectively. The swelling degree of those optimized formulations is found with slightervalues into acidic gastric medium (pH = 1.2), whereas increased values into alkaline intestinal mediums (pH = 6.8and 7.4), respectively, during 4-h time intervals. The experimental vitro release studies revealed for negligibleamount of DS that was released into simulated gastric fluid medium during 2 h, while slower drug releasedinto simulated intestinal fluid medium during 3 h and augmented released into stem cell factor medium during18 h studies, respectively. Furthermore, the drug release kinetics modeling studies performed for those optimizedformulations revealed for non-fickian mechanism type that was best fitted with Higuchi and Korsemeyer peppasmathematical models. These confirmed that drug releases was guided by dual mechanisms of diffusion anderosion simultaneously. Conclusion: The developed experimental formulations may be used for targeting of DSinto colon and possible management of inflammatory bowel disease, respectively.